Zirconium(IV)-BTC-based MOF modified with nickel as a catalyst for hydrogenation of citronellal - Lestari, Witri Wahyu; Aqna, Arifti Nur Laily; Prihadiyono, Fauzan Ibnu; Putra, Riandy; Firdaus, Maulidan; Rosari, Venansia Avelia; Arrozi, Ubed Sonai Fahrudin; Kadja, Grandprix T.M. (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study is designed to determine the effect of nickel (Ni) metal bearing on zirconium(IV) benzene 1,3,5-tricarboxylate based MOF, [Zr6 O4 (OH)4 (O2 C2 H3 )6 (BTC)2 ] (Zr-BTC) and its application as a catalyst in the citronellal hydrogenation. The synthesis of Zr-BTC was carried out under solvothermal condition, while the wet impregnation method was used to synthesize 2.5 wt.% Ni/Zr-BTC. The catalytic test of citronellal hydrogenation was performed in a batch reactor at 80 °C for 6 h with various hydrogen pressures. XRD characterization showed the suitability of the prominent peaks of Zr-BTC to the standard pattern, while Ni metal could not be detected clearly but was confirmed by EDX analysis. FTIR analysis showed a significant shift in the wavenumber from 1722 cm-1 to 1567 cm-1 indicating coordination of deprotonated ligands to the Zr4+ metal ions. Nickel loading reduced the surface area of Zr-BTC to 523 m2 /g and the pore volume to 0.11 cc/g according to the nitrogen sorption isotherm. The catalytic tests showed that 30% Ni loading enhanced the activity and selectivity of Zr-BTC in citronellal hydrogenation, resulting in 62.1% yield of isopulegol (for batch reactor) and 14.1% yield of citronellol (for hydrogen balloon).